NAHDLATUL ULAMA (NU) DAN KONTRIBUSINYA DALAM MEMPERJUANGKAN KEMERDEKAAN DAN MEMPERTAHANKAN NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) - Farih, Amin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
Religious mission of Nahdlatul Ulama (NU) in consolidating power against Dutch colonialism is a part of the struggle of NU for defending religious ideology and nationalism, as a form of patriotism (ḥubbu al-waṭan). NU had to expell the Dutch colonialists because it is a religious teaching. The law had already become a decision of the religious leaders (kyai) of NU, which ultimately rise